NanoCB-Fundacentro: a tool to support the assessment and control of occupational risk involving nanomaterials (Research, Society and Development, 2025)
The growing application of nanomaterials (NMs) across a wide range of economic sectors has raised significant concerns regarding occupational risks associated with their handling. This article presents NanoCB-Fundacentro, a tool developed to support the management of occupational risks in indoor environments where NMs are present.The tool was designed based on a critical analysis of 15 control banding methodologies, enabling the identification of the most relevant variables—severity and probability—as well as the most effective risk assessment approaches. Severity-related variables include morphology, mutagenicity/genotoxicity, carcinogenicity, respiratory sensitization, reproductive toxicity, and solubility. Probability-related variables encompass dustiness, frequency, duration, and quantity of exposure, among others.A key innovation of NanoCB-Fundacentro is its integration of existing control measures in the workplace as part of the risk assessment process, going beyond the variables traditionally considered by other tools. This enables a more comprehensive and realistic evaluation framework for categorizing both the severity of potential health effects and the likelihood of exposure.The tool classifies risk levels as low, medium, high, or very high, and uniquely provides specific recommendations tailored to each level. These recommendations guide users in implementing appropriate control and mitigation strategies.In conclusion, NanoCB-Fundacentro addresses a critical gap in the evaluation of occupational risks associated with nanomaterials. It distinguishes itself through its practical applicability, methodological breadth, and user-friendly interface, making it suitable for a wide range of work contexts.